THE ROLE OF SYLLABUS: THE DOCUMENTATION REQUIREMENTS OF ISO 9001:2008 - Koryati , M.Pd. (Politeknik Negeri Sriwijaya, 2011)
Abstract Syllabus is the part of curriculum that have to be designed before the teacher conduct the teaching and learning activity. The syllabus design will become the teacher’s written syllabus and document needed for the teacher to analyze the whole teaching and learning activity done for the semester and become a consideration for the next syllabus design as the follow up and better teaching and learning activity. For every education institution that has been preparing their institution to demonstrate conformity with the requirements of ISO 9001:2008, for the purposes of certification, contractual, or other reasons, is important to provide evidence of the effective implementation of the quality of the management system. The example of evidence provided is a complete document. Syllabus document is one of the evidence that have to be provided by the education institution.